عمل الهيئات البرلمانية والتشريعية في ظل جائحة كورونا عبد الله حميد الجيبي - Abdulla Humaid Al Junibi; Muhammad Najib Abdullah; Syahirah Abdul Shukor (World Conferences, 2024)
During the Corona pandemic, legislative bodies raised questions about whether parliaments and legislatures should continue to meet during the pandemic and how to get their work done. The problem emerged, that governments in many countries dealt with this situation as an emergency, so governments adopted far-reaching restrictions to combat the spread of the epidemic, which often violate a set of basic human rights and personal freedom, such as: freedom of movement, freedom of assembly and freedom of opinion. This raised concerns about the rule of law, when procedures were adopted through executive orders, government decrees and emergency regulations. The study aimed to discuss the challenges posed by the Corona pandemic. He presented the measures and procedures of the parliaments of the world during the spread of the epidemic. Through the descriptive and analytical method, the topic was discussed in two sections. By analysing the parliamentary realities of many elected federal, regional and international legislative bodies; We found that the role of councils and legislative bodies had suffered like others, while we found that the continued work of legislative bodies revealed the fact that these councils had given priority to enacting legislation, indifferent to the risk of the epidemic to their members